PERSISTENCE OF ISLAMIC BANKS’ EFFICIENCY AMID ECONOMIC SHOCKS - Siregar, Yulfani; Trapsila, Aji Purba (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
The aim of this work is the evaluation of the technical efficiencies of Islamic banking institutions in Indonesia and the determinants of efficiencies during the specific economic shock period of 2020 to 2023. Data from the years 2017 to 2023 are utilized in the study. Using the quantitative approach, Data Envelopment Analysis (DEA), the Islamic banks were evaluated to determine their technical efficiencies. The Islamic banks’ efficiencies were evaluated using Tobit Regression. The outcome indicated that sharia compliant banking in Indonesia is not technically efficient and that there is variation across the years in the efficiencies. As for the explanation for the efficiencies, the investigation indicated that BOPO negatively impacted efficiencies while FDR positively impacted efficiencies. In addition, the results indicated that inflation did not have as great of an effect. The efficiencies were impacted negatively by the pandemic as the economic shock of the COVID-19 virus created a greater economic shock. In this case, the relationship for the economic shock of the Russia-Ukraine conflict was not demonstrated. The Islamic banks ' efficiency during the economic shocks provide academic contributions and current literature.